Turismo de aventura: off-road como prática - Stigliano, Beatriz Veroneze (Revista Turismo em Análise, 2000)
This article focuses the analysis of adventure tourism concepts presented by some authors, the characterization of the variables that take part in the off road activity in Brazil and the discussion of the role played by nature in this activity. It is based on the literature and articles regarding adventure tourism and the off-road activity and on the opinion of pioneers and professionals, obtained by the application of interviews.